Kajian Penempatan Radar Cuaca S-Band Natuna Menggunakan Metode Analytical Hierarchy Process - Maulana Putra; Muhamad Habibi (LPPM Institut Pendidikan Nusantara Global, 2025)
The strategic placement of S-Band weather radar is crucial for improving the accuracy of extreme weather monitoring in archipelagic regions such as Natuna. This study aims to identify the optimal radar location by systematically considering technical and non-technical factors using the Analytical Hierarchy Process (AHP), which enables quantitative decision-making through hierarchical criteria structuring, pairwise comparisons, and consistency checks. The results indicate that power supply and land ownership status are the most influential sub-criteria in site selection. Among the two alternatives evaluated, Location A scored the highest at 0.593 compared to Location B’s 0.407, making it the preferred site for radar installation. The consistency of the results was validated with a consistency ratio within the acceptable threshold. These findings confirm that AHP is a reliable and replicable method for infrastructure decision-making, particularly in supporting meteorological systems in strategic island regions.